Level of Anxiety Regarding Tooth Extraction Among Children with Mental Disability - Sulistiani, Silvia; Ulliana, Ulliana; Marludia , Melani Agis; Putri , Maria Mawar (Poltekkes Kemenkes Kupang, 2023)
Anxiety is a natural trait that occurs in every person which can occur during dental nursing activities. This can also be experienced by children with mental disability who will have their teeth extracted. This study aims to determine the level of anxiety regarding tooth extraction among children with mental disability at SLB Al-Gaffar Guchany by gender and age. This was a descriptive study using quantitative data analysis with a total sampling technique which obtained 20 samples. Data were analyzed using the Chi-square test to determine whether there was a relationship between one variable and another. The results from the statistical test showed that that gender and age had no significant relationship with the level of anxiety regarding tooth extraction among children with mental disability with a p value of 0.848 and 0.456 >0.05, respectively. It can be concluded that there was no difference in the level of anxiety regarding tooth extraction among children with mental disability at SLB Al-Gafar Guchany by gender and age.